Creating An Interactive Online Museum For The Internet - Belinda, StaMaria (2001)
The purpose of this project is to create an awareness of the importance of Information Technology to institutions such as museums, archives, galleries and others. Information Technology enables museums to better reach out and educate people of the museum collection's heritage overcoming time and geographical limitations. The online museum concept is promoted here and digital library is used as a collective tool to create in one location information about the digital collections of many institutions. The online museum also creates a web-site presence for the museum and promote e-commerce facilities for the museums. The system was developed using the Web Page Development Methodology. The project also discusses the limitations and recommendations for the system.